In Vivo Evaluation of 1-O-(4-(2-Fluoroethyl-Carbamoyloxymethyl)-2-Nitrophenyl)-O-β-D-Glucopyronuronate: A Positron Emission Tomographic Tracer for Imaging β-Glucuronidase Activity in a Tumor/Inflammation Rodent Model - Iněs F. Antunes; Hidde J. Haisma; Philip H. Elsinga; Aren van Waarde; Antoon T.M. Willemsen; Rudi A. Dierckx; Erik F.J. de Vries (Molecular Imaging)
β-Glucuronidase (β-GUS) plays an important role in inflammation and degenerative processes. The enzyme has also been investigated as a target in prodrug therapy for cancer. To investigate the role of β-GUS in pathologies and to optimize β-GUS-based prodrug therapies, we recently developed a positron emission tomographic (PET) tracer, 1-O-(4-(2-fluoroethyl-carbamoyloxymethyl)-2-nitrophenyl)-O-β-D>-glucopyronuronate ([ 18 F]FEAnGA), which proved to be selectively cleaved by β-GUS. Here we present the in vivo evaluation of [ 18 F]FEAnGA for imaging of β-GUS in a tumor/inflammation model. Ex vivo biodistribution of [ 18 F]FEAnGA was conducted in healthy rats. PET imaging and pharmacokinetic modeling were performed in Wistar rats bearing C6 tumors of different sizes and sterile inflammation. The biodistribution studies of [ 18 F]FEAnGA indicated low uptake in major organs and rapid excretion through the renal pathway. MicroPET studies revealed three times higher uptake in the viable part of larger C6 gliomas than in smaller C6 gliomas. Uptake in inflamed muscle was significantly higher than in control muscle. The distribution volume of [ 18 F]FEAnGA in the viable part of the tumor correlated well with the cleavage of the tracer to [ 18 F]fluoroethylamine and the spacer 4-hydroxy-3-nitrobenzyl alcohol. [ 18 F]FEAnGA is a PET tracer able to detect increased activity of β-GUS in large solid tumors and in inflamed tissues.